Analisis Perkembangan Pelafalan Fonem pada Gala Sky melalui Rekaman Video Vlog - Suryani, Azizah; Karunia Putra, Dona Aji (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
A comprehensive grasp of language development in children is essential for the design of effective intervention strategies aimed at overcoming language difficulties in children. The objective of this research is to examine aspects of phonological development, including vowel phonemes, consonants, and diphthongs, in two-year-old. This research was conducted using a qualitative descriptive methodology. The data was sourced from YouTube account channels in the form of video recordings, such as vlogs. The data collection technique employed in this research is documentation, listening, and taking notes. The findings indicated that the GSA subjects demonstrated proficiency in the pronunciation of vowel, consonant, and diphthong phonemes. Nevertheless, there are still several vowel, consonant, and diphthong phonemes that have not been pronounced correctly. For instance, the vowels /i/ and /a/ have been mispronounced, as have the bilabial consonants /p/, /m/, apicodental consonants /t/, apicoalveolar consonants /l/, /n/, /r/, /s/, laminopalatal consonants /c/, /Ã±/, dorsovelar consonants /g/, and semivowel /w/. The subject's strategies for overcoming difficulties in pronunciation of words and phonemes include word contraction, phoneme deletion, and phoneme substitution.